Impurity band broadening as the origin of the positive magnetoresistance in the dilute magnetic semiconductor zinc manganese selenide - Petznick, Steve; Justus Liebig University Giessen (My University, 2015)
This work is dedicated to give a novel explanation for the large positive magnetoresistance effect in the n-type dilute magnetic semiconductor zinc manganese selenide. This effect has been observed in experiment in the hopping transport regime. The appearance of hopping transport is a necessary requirement for this effect to occur, as is the presence and the amount of magnetic atoms in the material. In literature, no conclusive explanation for this large positive magnetoresistance effect is known. The nature of the hopping transport requires a precise knowledge of the energetic position of each donor level, as an thermally activated electron has to overcome the energy difference from one donor level to another. Another aspect of the transport mechanism is that each donor-bound electron interacts only with the manganese atoms in its vicinity. Therefore, our explanation is based on the statistical distribution of magnetic atoms in the crystal. The random distribution of manganese leads to fluctuations of the donor levels according to their local manganese contents. Due to the bowing of the conduction band edge a donor level with a high local manganese content has a low energy. The fluctuating donor levels are represented by their density of states. This donor energy distribution is called impurity band and can be described by its width and its shape. An external magnetic field leads to a downshift of the preferred spin state of each donor, which is proportional to the Brillouin function and to its local manganese content. The energetic position inside the impurity band at zero magnetic field and the magnetic field induced energetic downshift, both depending on the local manganese content, are relevant. For example, a donor level with a high local manganese content is low in energy and experiences a large downshift in energy. The combination of these two aspects leads to an increasing of the width of the impurity band, while its shape remains unaffected in a first approximation. Using only basic hopping rates, this increasing impurity band-width results in an increasing resistivity, i.e. a positive magnetoresistance. To quantify this process two theoretical approaches are presented, i.e. a scaling approach and simulations of the effect.

Diese Arbeit ist dazu bestimmt, eine neue Erklärung für den großen positiven Magnetowiderstandseffekt im verdünnt magnetischen n-Typ Halbleiter Zinkmanganselenid zu liefern. Dieser Effekt wurde im Experiment beobachtet, genauer im Regime des Hopping-Transports. Dabei ist das Auftreten des Hopping-Transports eine notwendige Voraussetzung für diesen Effekt wie auch die Anwesenheit und die Menge magnetischer Atome in dem Material. In der Literatur ist keine schlüssige Erklärung für diesen großen positiven Magnetowiderstandseffekt bekannt. Die Natur des Hopping-Transports verlangt eine präzise Kenntnis der energetischen Position eines jeden Donatorniveaus, da ein thermisch aktiviertes Elektron die Energiedifferenz von einem Donator zum nächsten überwinden muss. Ein weiterer Aspekt des Transportmechanismus ist, dass jedes donatorgebundene Elektron nur mit den Manganatomen in seiner Umgebung interagiert. Daher basiert unsere Erklärung auf der statistischen Verteilung der Manganatome in dem Kristall. Die zufällige Verteilung von Mangan führt zu Fluktuationen der Donatorniveaus entsprechend ihrer lokalen Mangankonzentrationen. Aufgrund des Durchbiegens der Leitungsbandkante hat ein Donatorniveau mit hohem lokalem Mangangehalt eine niedrige Energie. Die fluktuierenden Donatorniveaus sind durch ihre Zustandsdichte dargestellt. Diese Verteilung der Donatorniveaus wird Störstellenband genannt und kann mittels ihrer Breite und Form beschrieben werden. Ein externes magnetisches Feld führt zu einer Verschiebung des bevorzugten Spinzustandes eines jeden Donators hin zu niedrigeren Energien, die proportional zu der Brillouinfunktion und zu seinem lokalen Mangangehalt ist. Die energetische Position innerhalb des Störstellenbandes ohne Magnetfeld und die magnetfeldinduzierte Verschiebung, beide abhängig von dem lokalen Mangangehalt, sind relevant. Zum Beispiel besitzt ein Donatorniveau mit einem hohen lokalen Mangangehalt eine niedrige Energie und erfährt eine große Verschiebung. Die Kombination dieser beiden Aspekte führt zu einer Verbreiterung des Störstellenbandes, während dessen Gestalt in erster Näherung unverändert bleibt. Nutzt man nun ausschließlich grundsätzliche Hopping-Raten, so resultiert aus dieser Verbreiterung des Störstellenbandes eine Zunahme des spezifischen elektrischen Widerstandes und damit ein positiver Magnetowiderstand. Um diesen Prozess zu quantifizieren werden zwei theoretische Ans¨atze vorgestellt, ein Skalierungsansatz und Simulationen des Effekts.
Keywords: Magnetowiderstand; DMS; magnetoresistance; DMS; ddc:530